Borassus powder-reinforced poly(lactic acid) composites with improved crystallization and mechanical properties - Marathe, Y. N.; Arun, Torris A. T.; Ramesh, C.; Badiger, M. V. (Journal of Applied Polymer Science, 2019)
This article reports on the development of biocomposites based on polylactic acid (PLA) and borassus powder. Borassus powder was treated with alkali to remove hemicelluloses and lignin. The treated borassus improved the homogeneous mixing with PLA and increased the crystallinity of PLA. Dispersibility of the borassus was studied by scanning electron microscopy (SEM) and X‐ray MicroCT. PLA/borassus composites were prepared by melt mixing of PLA with 5, 10, and 15 wt % treated/untreated borassus. Composites were examined for mechanical properties and crystallization. Composites showed enhanced tensile strength compared to neat PLA. The PLA/treated borassus powder composites displayed higher crystallinity than PLA. The isothermal cold crystallization study showed increase in the crystallization rate of PLA in the presence of treated borassus. The spherulitic growth was studied using polarized optical microscopy. The enhanced performance of the PLA‐borassus composites was observed in the presence of borassus. This study demonstrates that the PLA‐borassus composites show great promise for bioplastics applications.